An efficient tree-based clone detection scheme in wireless sensor network. Issue 5 (4th July 2019) - Lalar, Sachin; Bhushan, Shashi; Surender
Abstract: Wireless sensor network has widely used in various applications such as military, environment monitoring where sensor nodes has operated in open, harsh environment. Different type of attacks can be originated by attacker in this environment. The Clone attack is suspected the most serious attacks in WSN as clone node attack can fabricate a variety of attack in networks. In this attack, an adversary confines the legitimate sensors and creates the replicas with captured node of identical identity and deploys the clone nodes in the network. We propose a clone detection scheme to detect the replica nodes in the wireless sensor network. The proposed method, TBCND, has two phases. In first phase, network is deployed in Binary search tree form which uses the key as node id. When any clones communicate in the network it will detected in next phase. The proposed method implement in ns2 simulator and performance of TBCND is measure in E2E delay, PDR, packet loss and residual energy. We evaluate the performance in three scenarios and compare the result in normal and clone containing network. The result show that clone node has no effect on network due to proposed method. We also compute the communication and memory cost of proposed method and compare to the existing methods. The result shows that the proposed method has lower communication, memory cost as compared to existing methods